EXPLORING THE MASS EARLY RETIREMENT CONFLICT AMONG SENIOR TEACHERS IN MALAYSIA: A MAJOR CONCERN TO STAKEHOLDER - Ramlan Mustapha,; Maziah Mahmud,; Jazimin Zakaria,; Mohamad Sahizam Musa,; Hapini Awang, (Journal of Islamic, Social, Economics and Development, 2023)
Despite the existence of incentives and improvements intended to prevent early retirement, the number of teachers taking early retirement has increased in recent years. Therefore, it is important to investigate the root causes of early retirement among educators to comprehend the elements that influence teachers to make such a decision. We explore how Malaysian school teachers reflect on their ability to shape their late careers as conditioned by conflicting institutional arrangements related to early retirement and extended working life. Using a case study approach and drawing on qualitative interview data, we focus on the biographical experiences of fifteen senior school teachers (aged 50 plus). The data is analyzed using thematic analysis. Findings indicate that senior teachers' early retirements were simultaneously reinforced and counteracted by various interacting factors including burnout, technology efficacy, workload, health and organizational conflict. Authorities must immediately implement improvements and measures to prevent this problem from persisting. Continuous improvement and concrete actions need to be implemented comprehensively so that this problem does not continue in the future.